2021
DOI: 10.1007/s42770-021-00588-y
|View full text |Cite
|
Sign up to set email alerts
|

Decreased biofilm formation in Proteus mirabilis after short-term exposure to a simulated microgravity environment

Abstract: Background Microbes threaten human health in space exploration. Studies have shown that Proteus mirabilis has been found in human space habitats. In addition, the biological characteristics of P. mirabilis in space have been studied unconditionally. The simulated microgravity environment provides a platform for understanding the changes in the biological characteristics of P. mirabilis. Objective This study intends to explore the effect of simulated microg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Bacterial strain and culture conditions . The original P. mirabilis strain, used in this study, was obtained from the Space Biomedical Laboratory of the Second Medical Center of the Chinese PLA General Hospital and has already been described many times ( Wang et al 2021 ). The strain was cultivated at 37°C for 24 h under constant shaking (200 rpm) in Luria-Bertani (LB) medium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial strain and culture conditions . The original P. mirabilis strain, used in this study, was obtained from the Space Biomedical Laboratory of the Second Medical Center of the Chinese PLA General Hospital and has already been described many times ( Wang et al 2021 ). The strain was cultivated at 37°C for 24 h under constant shaking (200 rpm) in Luria-Bertani (LB) medium.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is necessary to study the biological characteristics and genetic features of P. mirabilis in MG. To date, multiomics analysis has already been developed to study the molecular mechanisms of microbial survival and adaption in MG and SMG environments ( Milojevic and Weckwerth 2020 ). Although a recent study has analyzed the phenotype and transcriptome of P. mirabilis after short-term exposure to SMG, long-term SMG exposure and varying lengths of SMG exposure to P. mirabilis remain unclear ( Wang et al 2021 ). In this study, the growth behavior and transcriptome profile of P. mirabilis exposed to long-term SMG were compared with those exposed to short-term SMG to analyze the effect of MG exposure duration on its characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…19,23,24 . Finally, spaceflight alters biofilm formation capability in many bacteria; in some, like Pseudomonas aeruginosa, it increases the likelihood a superstructure will form, whereas in others, like Proteus mirabilis, it has the opposite effect 25,26 . Indeed, early studies in aerospace medicine have indicated that the microbiome of humans and the built environment shift as a function of spaceflight 27 .…”
Section: Introductionmentioning
confidence: 99%
“…M. marinum also exists in the environment (Falkinham 2021) and is a model for biofilm-forming mycobacteria. Since biofilm formation can be altered by low shear modeled microgravity (LSMMG, Castro et al, 2011;Wang et al, 2021;Cheng et al, 2014;Topolski et al, 2022), biofilm-forming bacteria are a concern for spaceflight due to the need to protect the crew's potable water and water processing hardware. M. marinum was chosen as the test organism in this study as these bacteria can grow as a biofilm or as a planktonic culture.…”
Section: Introductionmentioning
confidence: 99%